Tingkat Stres Berdasarkan Sif Kerja pada Perawat di Ruang Isolasi COVID-19 - Refika Ilma Nurul Uswah; Siska Nia Irasanti (UNISBA Press, 2022)
Abstract. COVID-19 is an acute respiratory disease that was first reported in Wuhan, China. High rates of infection and mortality increase social and mental pressure on health workers and cause mental health problems such as stress. Based on the results of research in Taiwan, nurses have a higher mean stress value than other health workers. Stress is a homeostatic imbalance condition caused by physical stimulation that results a changes in individuals. One of the stressors for nurses is work shift. The purpose of this study was to describe the work shift and the description of stress levels based on the work shift of nurses in the COVID-19 Isolation Room. Descriptive method with a cross-sectional design approach is used in this study, with 79 respondents taken by total sampling technique. The data was taken using a questionnaire instrument from Tayyib and Alsolami (2020), the questionnaire consists of 14 questions and has been modified by the researcher and has been tested valid and reliable .The results of this study showed that most of the nurses who experienced stress working on the morning and evening shifts were 27 nurses (71.05%) and 19 nurses (63.33%) and 5 out of 11 nurses (45.45%) in the afternoon shift. From these results, the hospital is expected to increase attention and evaluation regarding efforts to overcome stressors for nurses, especially during the COVID-19 pandemic. Abstrak. COVID-19 adalah penyakit respiratori akut yang dilaporkan pertama kali ditemukan di Wuhan, China. Tingginya angka infeksi dan mortalitas meningkatkan tekanan sosial dan mental pada tenaga kesehatan dan dapat menimbulkan gangguan kesehatan mental seperti stres. Berdasarkan hasil penelitian di Taiwan, perawat memiliki nilai mean stres yang lebih tinggi dibandingkan tenaga kesehatan lain. Stres adalah kondisi tidak seimbangnya homoestatis yang diakibatkan oleh adanya rangsangan fisik yang mengakibatkan perubahan pada individu. Salah satu stresor pada perawat adalah sif kerja. Tujuan dari penelitian ini adalah untuk mengetahui gambaran sif kerja dan gambaran tingkat stres berdasarkan sif kerja pada perawat di Ruang Isolasi COVID-19. Metode deskriptif dengan pendekatan cross-sectional design digunakan dalam penelitian ini, dengan 79 responden yang diambil dengan teknik total sampling. Data diambil dengan instrument kuesioner dari Tayyib dan Alsolami (2020), kuesioner terdiri dari 14 pertanyaan dan telah dimodifikasi oleh peneliti dan telah teruji valid dan reliabel. Hasil penelitian ini menunjukan sebagian besar perawat yang mengalami stres bekerja pada sif pagi dan malam yaitu 27 perawat (71,05%) dan 19 perawat (63,33%) serta sif sore 5 dari 11 perawat (45,45%). Dari hasil ini, pihak Rumah Sakit diharapkan meningkatkan perhatian dan evaluasi mengenai upaya penganggulangan faktor yang menjadi stresor pada perawat terutama selama pandemi COVID-19.